2009
DOI: 10.1159/000232310
|View full text |Cite
|
Sign up to set email alerts
|

Future Perspectives in the Treatment of Psoriasis

Abstract: All available antipsoriatic therapies are of symptomatic character. Treatments established so far are limited in their use due to side effects or lack of efficacy resulting in poor quality of life for affected people. Development of new therapeutic approaches would not only broaden our armamentarium against psoriasis, but could also increase our understanding of the pathogenesis of this disease. In brief, 2 main targets represent attractive candidates, either the keratinocyte itself or the immune system. Promi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
0
2
0
2
Order By: Relevance
“…Psoriasis patients also experience a decreased quality of life as a result of this disease [5]. The pathogenesis of psoriasis is currently under active investigation, with studies aiming to identify genetic susceptibility loci for psoriasis in order to detect novel targets for systemic therapy [69]. While the exact pathogenesis of psoriasis is not fully understood, basic and translational investigations have led to a renewed understanding of Th-17 and Th-1 pathways involved in the development of psoriasis [10].…”
Section: Introductionmentioning
confidence: 99%
“…Psoriasis patients also experience a decreased quality of life as a result of this disease [5]. The pathogenesis of psoriasis is currently under active investigation, with studies aiming to identify genetic susceptibility loci for psoriasis in order to detect novel targets for systemic therapy [69]. While the exact pathogenesis of psoriasis is not fully understood, basic and translational investigations have led to a renewed understanding of Th-17 and Th-1 pathways involved in the development of psoriasis [10].…”
Section: Introductionmentioning
confidence: 99%
“…It affects about 2 % of the world population (Baker et al, 2008, Wippel-Slupetzky & Stingl, 2009. Previous studies have demonstrated that psoriasis prevalence varies as a result of two factors: (1) geographical localization and (2) ethnic group.…”
Section: Prevalencementioning
confidence: 99%
“…A patogénese da psoríase tem sido matéria de debate, nomeadamente, se a doença se inicia como um distúrbio primário dos queratinócitos ou como consequência de uma resposta imunológica alterada contra um, ainda não identificado, antigénio 10 . Hoje em dia, a primeira teoria tem sido abandonada, aceitando a maioria dos autores que se trata de uma doença imuno-mediada.…”
Section: Conhecimento Da Patogénese Da Psoríaseunclassified
“…A formação do complexo receptor das IL/JAK leva à fosforilação das STAT, proteínas citoplasmáticas latentes, envolvidas na transmissão de sinais extracelulares ao núcleo. As proteínas STAT fosforiladas são então translocadas para o núcleo onde iniciam a transcrição de mais citocinas inflamatórias 4,10,25…”
Section: Inibidores Da Il-22unclassified